AIII-BV(N) photodetectors with functionally graded active area - Wośko, Mateusz; Paszkiewicz, Bogdan; Piasecki, Tomasz; Prażmowska, Joanna; Paszkiewicz, Regina; Tłaczała, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
Functionally graded materials (FGM) find widespread for mechanical applications. Nowadays, they become more and more attractive in fabrication of electronic and optoelectronic devices. This is due to by their unique properties. FGM are potential candidates for high sensitive photonic devices which could operate in a wide spectral range (also for voltage tunable photodetectors). In this paper, the analysis of several photodetector constructions fabricated in FGM has been presented. The influence of AIII-BV(N) grading layers composition and configuration of the detector on its optical and electrical properties has been discussed. Also, a comparison between conventional non-graded and graded devices has been made. All simulations presented in the work are performed by the specialized software designed for modeling AIII-BV(N) graded structures. The software allow us to calculate both the parameters of FGM structure and device characteristics. During the simulation process it was noticed that the bandgap gradation in phototodetector active area improved its sensitivity up to 150% compared to classical, non-graded structures. Also, another effect such the wavelength sensitivity observed in these devices makes them very attractive for applications in which the high sensitive wavelength dependence is a key factor.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 161-165
Keywords: optyka; FGM; graded materials; photodetector; simulation